Risk Factors for Hearing Loss at Birth in Newborns with Congenital Cytomegalovirus Infection: A Comprehensive Systematic Review - Della Reyhani Putri; Ilham Priharto (International Medical Journal Corp. Ltd, 2025)
Introduction: Congenital cytomegalovirus (cCMV) infection is the foremost non-genetic etiology of sensorineural hearing loss (SNHL) in the pediatric population, representing a significant global public health challenge (Pignataro et al., 2024). The clinical presentation of cCMV is markedly heterogeneous, ranging from asymptomatic infection to severe, multi-system disease. The early identification of newborns at the highest risk for congenital SNHL represents a significant clinical challenge, as hearing loss can be present at birth or have a delayed onset (Goderis et al., 2014). This systematic review aims to comprehensively identify, appraise, and synthesize the existing evidence on maternal, neonatal, and diagnostic risk factors that are predictive of SNHL present at birth in newborns with confirmed cCMV. Methods: A systematic literature search was conducted across the PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library databases for cohort, case-control, and cross-sectional studies published through 2024. Studies were deemed eligible for inclusion if they investigated specific risk factors for congenital SNHL in newborns with virologically confirmed cCMV infection within the first 21 days of life (Rawlinson et al., 2017). The methodological quality and risk of bias of included non-randomized studies were rigorously assessed using the Risk Of Bias In Non-randomized Studies - of Interventions (ROBINS-I) tool. Data were extracted and narratively synthesized, categorized by the specific domain of the risk factor. Results: A total of 17 studies, encompassing over 3,000 newborns with cCMV, met the inclusion criteria. The synthesis of evidence revealed several consistent and significant predictors of congenital SNHL. Key risk factors included maternal primary infection occurring within the first trimester of pregnancy (De Cuyper et al., 2022; Foulon et al., 2019), the presence of symptomatic disease at birth, particularly with evidence of central nervous system (CNS) involvement (Pignataro et al., 2024; Rivera et al., 2002), and specific abnormalities on neonatal neuroimaging, such as periventricular cysts on magnetic resonance imaging (MRI) (De Cuyper et al., 2022) and temporal-pole white matter abnormalities (Fink et al., 2024). The clinical finding of petechiae at birth also emerged as a strong independent predictor of congenital SNHL (De Cuyper et al., 2022). In contrast, the predictive utility of neonatal viral load measurements was found to be inconsistent across the analyzed studies (Boppana et al., 2005; Walter et al., 2008). Discussion: The synthesized evidence strongly indicates that the risk of congenital SNHL is not uniformly distributed among all newborns with cCMV. A distinct risk gradient exists, which is powerfully linked to the timing of maternal infection and the degree of viral impact on the neonatal central nervous system (Rivera et al., 2002). Neuroimaging, particularly brain MRI, emerges from this review as a paramount prognostic instrument for early risk stratification, capable of identifying specific lesions that confer a high risk of adverse outcomes (Fink et al., 2024; Manara et al., 2021). Conclusion: Maternal primary infection in the first trimester, clinical signs of CNS involvement at birth, specific neuroimaging findings, and the presence of petechiae are significant and clinically relevant risk factors for congenital SNHL in newborns with cCMV. These identified factors can be effectively utilized for early risk stratification, guiding targeted audiological surveillance, and facilitating informed parental counseling (De Cuyper et al., 2022).